Comparison of fast neutron spectra in graphite and FLINA salt inserted in well-defined core assembled in LR-0 reactor. (September 2015) - Košťál, Michal; Veškrna, Martin; Cvachovec, František; Jánský, Bohumil; Novák, Evžen; Rypar, Vojtěch; Milčák, Ján; Losa, Evžen; Mravec, Filip; Matěj, Zdeněk; Rejchrt, Jiří; Forget, Benoit; et al.
Highlights: Neutron spectra measured in graphite and LiF + NaF. Comparison of calculated and measured neutron spectra. Effect of 19F on variation between various library calculated spectra. Abstract: The present paper aims to compare the calculated and measured spectra after insertion of candidate materials for the Molten salt reactor/Fluoride cooled high temperature reactor system concept into the LR-0 reactor. The calculation is realized with MCNP6 code using ENDF/B-VII.0, JEFF-3.1, JENDL-3.3, JENDL-4, ROSFOND-2010 and CENDL-3.1 nuclear data libraries. Additionally, comparisons between the slowing down power of each media were performed. The slowing down properties are important parameters affecting the thickness of moderator media in a reactor.